The Effect of Perioperative Rescue Transesophageal Echocardiography on the Management of Trauma Patients. Issue 12 (15th June 2016) - Griffee, Matthew J.; Singleton, Andrew; Zimmerman, Joshua M.; Morgan, David E.; Nirula, Raminder
Abstract : To evaluate the effect of rescue transesophageal echocardiography (TEE) on the management of trauma patients, we reviewed imaging and charts of unstable trauma patients at a level I trauma center. Critical rescue TEE findings included acute right ventricular failure, stress cardiomyopathy, type B aortic dissection, mediastinal air, and dynamic left ventricular outflow tract obstruction. Left ventricular filling was classified as low (underfilled) in 57% of all cases. Rescue TEE revealed a variety of new diagnoses and led to a change in resuscitation strategy about half of the time. Abstract : Supplemental Digital Content is available in the text.